Assessing Recovery: Examination of Greenhouse Gas Fluxes, Soil Characteristics, and Vegetation in Sediment Enhanced Marshes - Danielle C. Perry; Nia Bartolucci; Cathleen Wigand; Kenneth B. Raposa; Joseph Loffredo; Wenley Ferguson; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Relationships Between Soil and Vegetation Properties and Soil Carbon Stocks Differ Between Grasslands with Different Water Table Management - Emma M. N. Polman; Kenneth F. Rijsdijk; Perry Cornelissen; Rutger L. van Hall; Franciska T. de Vries (Ecosystems, 2026)
Water table management such as temporal flooding is an important strategy for influencing vegetation development and creating suitable habitat for wildlife in managed wetland systems. Water table fluctuations can also affect soil carbon and nutrient cycling through changes in abiotic soil properties, plant traits and soil microbial communities, but research on the effect of temporal flooding on these relations is limited. Here we tested the hypothesis that winter inundation leads to a plant community with more fast-growth-related plant traits, a bacterial-dominated soil microbial community, and lower soil organic carbon stocks compared to a year-round dry grassland. We compared soil and vegetation of winter-inundated and non-inundated grassland in a Dutch-managed wetland area. In contrast to our hypothesis, we found that winter inundation results in plant communities with more slow-growth-related traits and microbial communities more dominated by fungi, compared to non-inundated grassland. We found no difference between shallow soil organic carbon stocks, carbon-to-nitrogen ratios or nitrogen-to-phosphorous ratios. Winter inundation did, however, change the relationship between soil and vegetation properties and soil carbon stocks, as well as soil nutrient ratios. While soil carbon stocks in non-inundated grassland were explained by abiotic soil and vegetation properties, soil carbon stocks were only explained by microbial properties in winter-inundated grasslands. These findings show that winter inundation can be used for vegetation and wildlife management with limited effects on soil carbon stocks.

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Back from the brink: Estimating daily and annual abundance of natural-origin salmon smolts from 30-years of mixed-origin capture-recapture data - Dalton J. Hance; John M. Plumb; Russell W. Perry; Kenneth F. Tiffan (Fisheries Research, 2024)

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

Using knowledge to care for country: Indigenous-led evaluations of research to adaptively co-manage Kakadu National Park, Australia - Cathy J. Robinson; Jennifer Mairi Macdonald; Michael Douglas; Justin Perry; Samantha Setterfield; Dennis Cooper; Maria Lee; Jonathan Nadji; Sean Nadji; Alfred Nayinggul; Anita Nayinggul; Kenneth Mangiru; et al. (Sustainability Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Proximal fluorescence sensing of potassium responsive crops to develop improved predictions of biomass, yield and grain quality of wheat and barley - Jonathan Eddison Holland; Davide Cammarano; Glenn J. Fitzgerald; Eileen M. Perry; Graeme Poile; Mark Kenneth Conyers (Precision Agriculture, 2019)

Dodo remains from an in situ context from Mare aux Songes, Mauritius - Hanneke J. M. Meijer; Arike Gill; Perry G. B. de Louw; Lars W. Van Den Hoek Ostende; Julian P. Hume; Kenneth F. Rijsdijk (The Science of Nature, 2012)

Effects of a novel mGlu2/3 receptor agonist prodrug, LY2140023 monohydrate, on central monoamine turnover as determined in human and rat cerebrospinal fluid - Stephen Lowe; Robert Dean; Bradley Ackermann; Kimberley Jackson; Fanni Natanegara; Shelby Anderson; James Eckstein; Eunice Yuen; Mosun Ayan-Oshodi; Mary Ho; David McKinzie; Kenneth Perry; et al. (Psychopharmacology, 2012)

Observing Biogeochemical Cycles at Global Scales with Profiling Floats and Gliders: Prospects for a Global Array - Kenneth Johnson; William Berelson; Emmanuel Boss; Zanna Chase; Hervé Claustre; Steven Emerson; Nicolas Gruber; Arne Körtzinger; Mary Jane Perry; Stephen Riser (Oceanography, 2009)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

Groundwater abstraction impacts on spring flow and base flow in the Hillsborough River Basin, Florida, USA - Kenneth A. Weber; Robert G. Perry (Hydrogeology Journal, 2006)

Nucleotide Substitution Rates in Legume Chloroplast DNA Depend on the Presence of the Inverted Repeat - Antoinette S. Perry; Kenneth H. Wolfe (Journal of Molecular Evolution, 2002)

Fluoxetine, but not other selective serotonin uptake inhibitors, increases norepinephrine and dopamine extracellular levels in prefrontal cortex - Frank P. Bymaster; Wei Zhang; Petra A. Carter; Janice Shaw; Eyassu Chernet; Lee Phebus; David T. Wong; Kenneth W. Perry (Psychopharmacology, 2002)

Olanzapine increases in vivo dopamine and norepinephrine release in rat prefrontal cortex, nucleus accumbens and striatum - Xi-Ming Li; Kenneth W. Perry; David T. Wong; F. P. Bymaster (Psychopharmacology, 1998)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)